Preliminary design of a boundary-layer wind tunnel for the University of the Philippines, Diliman - Quendangan, Nico C.; Hernandez, Jaime Y. Jr.; Mata, William L.; Tan, Liezl Raissa E. (Quezon City College of Engineering, University of the Philippines Diliman, 2014)
The research project focuses on providing a preliminary design of a boundary layer wind tunnel (BLWT) for the utilization of the University of the Philippines, Diliman on researches about the effects of wind to existing structures. The study intends to review related topics as presented in textbooks, and previous studies such as in journal articles regarding design and fabrication of BLWT. From this, the research identified relevant parameters needed to be considered for a good and optimum design. Two preliminary designs were made in this research: one was an open-circuit boundary layer wind tunnel with blowing type configuration limited by the space allotted in the new Structures Laboratory building; while another is of the same configuration but it has no space limitations and has a test section of 3 meters by 3 meters. Based on the actual procedure, done in this study, in obtaining a design, the research was to serve as a guideline in designing a BLWT so as to help future researchers having studies parallel to this.
Thesis (B.S. Civil Engineering)--University of the Philippines Diliman
Keywords: Wind tunnels -- Design and construction